Pseudomonas Aeruginosa: Virulence Factors and Antibiotic Resistance Genes - Rocha, Antônio José; Barsottini, Mario Ramos de Oliveira; Rocha, Renan Rhonalty; Laurindo, Maria Vitória; Moraes, Francisco Leandro Laurindo de; Rocha, Soraya Lília da (Brazilian Archives of Biology and Technology, 2019)
Abstract In this review, we explore some aspects of Pseudomonas aeruginosa virulence factors that are related to disease development in healthy organisms and resistance to antibiotics. This pathogen is one of the most clinically and epidemiologically important bacteria in Brazil, being the major cause of opportunistic infections. Among the virulence factors, biofilm formation acting of manner different in the organism. Furthermore, we review several P. aeruginosa genes that act in antimicrobial resistance, such as β-lactamases against β-lactamers. The resistance to pied-lactamases in P. aeruginosa is associated to resistance to the broad-spectrum cephalosporin. On the other hand, there is a group of synthetic broad-spectrum antibiotics acting on DNA synthesis is the quinolones that destroy the microorganism. We also explore the occurence of super bacterium: P. aerufinosa carrying genes blaKPC and blaNDM, which are associated with patient death above the average of other bacterial infections in hospitals. Those genes encode carbapenemases that can potentially hydrolyse all β-lactam antibiotics